2020
DOI: 10.1371/journal.pone.0240676
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin potentializes the respective cytotoxic activity of gemcitabine or doxorubicin on 3D culture of AsPC-1 or HepG2 cells, through the inhibition of HIF-1α and MDR1

Abstract: The impact of cancer on lifespan is significantly increasing worldwide. Enhanced activity of drug efflux pumps and the incidences of the tumor microenvironment such as the apparition of a hypoxic gradient inside of the bulk tumor, are the major causes of chemotherapy failure. For instance, expression of Hypoxia-inducible factor (HIF-1α) has been associated with metastasis, resistance to chemotherapy and reduced survival rate. One of the current challenges to fight against cancer is therefore to find new molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Many studies have reported that inhibition of HIF1A can significantly inhibit the growth of tumors, including HCC [33,34]. Quercetin, as an effective flavonoid component in EH, combined with specific anticancer drugs can increase the expression of p53 by downregulating the expression of HIF1A, thus inducing an increase in the proapoptotic process of liver cancer cells [35]. In addition, the expression of HIF1A can be regulated by activation of the PI3K-AKT pathway, which can be activated by RTK [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that inhibition of HIF1A can significantly inhibit the growth of tumors, including HCC [33,34]. Quercetin, as an effective flavonoid component in EH, combined with specific anticancer drugs can increase the expression of p53 by downregulating the expression of HIF1A, thus inducing an increase in the proapoptotic process of liver cancer cells [35]. In addition, the expression of HIF1A can be regulated by activation of the PI3K-AKT pathway, which can be activated by RTK [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 84 potential targets were obtained by taking the intersection. The majority of the compounds were flavonoids, such as quercetin, luteolin, kaempferide, and kaempferol, which have long been reported to have significant antitumor activity [ 33 36 ]. In this research, only eight compounds were found to meet the requirements of OB ≥30% and DL ≥ 0.18.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover quercetin could inhibit the MDR-1 efflux activity. In conclusion, they found quercetin could be administered in combination with GEM or DOX in multidrug resistant pancreatic and hepatic cancers, respectively ( Hassan et al, 2020 ).…”
Section: Quercetin and Gastrointestinal Cancermentioning
confidence: 98%
“…They also evaluated the effects of quercetin on the activity of drug efflux pumps as well as the effects related to hypoxia. Moreover, they investigated the role of multidrug transporters (including MDR) and HIF-1α ( Hassan et al, 2020 ). In their research, they combined quercetin with other anticancer drugs and showed that combination therapy (anticancer drug plus quercetin) had better results than single therapy.…”
Section: Quercetin and Gastrointestinal Cancermentioning
confidence: 99%